PELAKSANAAN FUNGSI KELUARGA (STUDI KASUS PELAKSANAAN FUNGSI KELUARGA PADA SUAMI PELAKU POLIGAMI DI KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Ainun Maknunah; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Polygamy is the phenomenon of life going on around us. The term polygamy is often heard but not many people who can accept this situation. The word itself comes from the Greek polygamy "polygamie", namely poly meaning many and gamie means the men, so the meaning of polygamy is men who take more than one woman in the bonds of marriage. In districts Kerumutan Pelalawan khasus polygamy occur. However, according to the interview with the Kantor Urusan Agama (KUA) local no husband reported to the local KUA second marriage. Because most of their second marriages performed outside the region and usually without the knowledge of his first wife. The first wife learned of her husband's second marriage after the husband's second wife brought to the area. Most people did not make polygamy, but some people do not agree with the incident. This study aims to determine the division of the implementation of family function in families that practice polygamy, by taking the focus on one family in which the husband to practice polygamy to have four wives. The research method in this research is descriptive research method. Descriptive research is research that aims to uncover the facts, circumstances, and phenomena. The author will menlakukna holistically related research and economic pembagaian time in polygamous families.Keywords: Family, Polygamy, Family Function Implementation